2012
DOI: 10.1177/1753193412453359
|View full text |Cite
|
Sign up to set email alerts
|

Sibling recurrence risk in Dupuytren’s disease

Abstract: Dupuytren's disease is a complex condition, with both genetic and environmental factors contributing to its aetiology. We aimed to quantify the extent to which genetic factors predispose to the disease, through the calculation of sibling recurrence risk (ls), and to calculate the proportion of heritability accounted for by currently known genetic loci. From 174 siblings of patients with surgically confirmed disease, 100 were randomly selected. Controls were recruited from patients attending an ophthalmology ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
2
13
0
2
Order By: Relevance
“…The results indicate a strong genetic influence in DD, which agrees with observations made in earlier family studies (Capstick et al, 2013; Hindocha et al, 2006; Hu et al, 2005). The advantage of the present study was the use of large nationwide population-based registers with long and complete follow-ups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results indicate a strong genetic influence in DD, which agrees with observations made in earlier family studies (Capstick et al, 2013; Hindocha et al, 2006; Hu et al, 2005). The advantage of the present study was the use of large nationwide population-based registers with long and complete follow-ups.…”
Section: Discussionsupporting
confidence: 92%
“…In two recent studies the risk of DD was found to be between 2.9 and 4.5 times higher in individuals with an affected sibling than in the general population (Capstick et al, 2013; Hindocha et al, 2006). A positive family history was noted in 41% and 47% of patients with DD, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…7 Both genetic and environmental factors are likely to contribute to DD. [8][9][10] Environmental factors known to affect the development of DD include repeated hand injuries, diabetes, epilepsy, alcohol consumption, and tobacco use. [11][12][13] These factors play a role in inflammation, fibrosis, cellular trauma, and ischemia, affecting the interaction between the myofibroblast and collagen matrix.…”
mentioning
confidence: 99%
“…10 Further work is required to be able to explain all these findings, including the double spiral around the digital nerve during surgery. 28 Additionally, the disease occurs more frequently when diseases such as diabetes mellitus are present or following long-term barbiturate use.…”
Section: Surgical Anatomymentioning
confidence: 99%